Agriculture Biomass for Sustainable Electricity Supply Systems: A Dynamic System Approach - Destianto, Arief Sandi; Mudjahidin, Mudjahidin (Institut Riset dan Publikasi Indonesia, 2025)
East Java has great potential in utilizing agricultural waste as a source of biomass energy to support the transition to New Renewable Energy (NRE). However, the development of biomass power plants faces challenges such as investment feasibility evaluation and biomass potential measurement. The East Java Government has set sustainable energy targets through Governor Regulations. This study developed a dynamic system-based simulation model to analyze factors influencing the utilization of agricultural waste as biomass energy. Verification results using Vensim PLE software show the model is valid with an error rate of E1 < 5% and E2 < 30%. In the Do-Nothing scenario, the electricity deficit could worsen in the future without increasing power plant capacity, especially from renewable energy. Conversely, the biomass power plant infrastructure development scenario shows that by 2024, the electricity deficit can be reduced from -7,599.47 GWh to -2,722.98 GWh. This trend continues in subsequent years, with the biomass scenario consistently decreasing the deficit and even generating a surplus in some years. Therefore, developing biomass-based power plants is a strategic step to reduce dependence on fossil fuels and enhance regional energy security in East Java.